When Bureaucracy Fails Democracy: Explaining the Institutional Barriers to Electoral Inclusion in Remote Island Regions - Baharudin Hamzah; Aloysius Liliweri; Laurensius Petrus Sayrani; Rudi Rohi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
Despite extensive democratic reforms and administrative decentralization, Indonesia continues to struggle with persistent voter exclusion in its remote island regions. Existing studies often attribute this issue to technical or logistical limitations, overlooking the bureaucratic and institutional roots of the problem. This study addresses that gap by examining how bureaucratic design and institutional misalignment contribute to the reproduction of electoral exclusion within decentralized yet fragmented administrative systems. Focusing on Flores Timur, an archipelagic district in East Nusa Tenggara, this research employs a qualitative case study approach, utilizing 28 in-depth interviews with election officials, civil registry staff, and local stakeholders, supported by document analysis. Findings reveal that voter exclusion from the Daftar Pemilih Tetap (Final Voter List) is structurally embedded, stemming from the institutional disconnect between the Komisi Pemilihan Umum Daerah (KPUD) and the Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil). The absence of a shared, binding data system has created what this study terms an administrative blind spot. In this zone, no agency fully claims responsibility for data accuracy, resulting in passive but recurring disenfranchisement. The study’s novelty lies in theorizing latent disenfranchisement, a form of exclusion produced not by intent but by bureaucratic rigidity, fragmented accountability, and non-interoperable systems. Extending the concept of bureaucratic disenfranchisement, the study offers new insights and policy recommendations for inclusive, coordinated electoral reform.